Pengaruh Latar Belakang Pendidikan Terhadap Kinerja Guru Pada SMP Negeri 2 Susua Kecamatan Susua - Osarao Laia; Yamolala Zega; Eliagus Telaumbanua; Odaligoziduhu Halawa (Visi Sosial Humaniora, 2024)
The purpose of this study was to determine the effect of educational background on teacher performance at SMP Negeri 2 Susua, Susua District. This type of research uses quantitative research and sampling techniques using probability sampling with a sample size of 43 respondents. Data collection techniques used were observation, questionnaires and documentation. Based on the results of the study, a correlation coefficient value of 0.583 was obtained, which means that the level of relationship between educational background and teacher performance is at a sufficient level. At SMP Negeri 2 Susua, Susua District, it is important to understand how teacher education can affect the quality of teaching and student learning outcomes. Research in recent years has shown that educational background can have a significant impact on the way teachers teach and their effectiveness in educating. Academic education includes all types of training and education that teachers receive before they start teaching, including bachelor's degrees, professional training, and additional certifications